2010
DOI: 10.1258/hsmr.2009.009027
|View full text |Cite
|
Sign up to set email alerts
|

A configurational view of executive selection behaviours: a taxonomy of USA acute care hospitals

Abstract: Health-care organizations, particularly hospitals, are among the most complex organizations to manage. However, the executive selection processes these organizations have in place are poorly understood. The purpose of this study is to explore the executive selection processes employed by USA acute care hospitals and discern if such processes are related to environmental, structural and strategic organizational characteristics. We conceptualize this model using a configurational approach. We present an empirica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…According to this approach, organizations are characterized by interrelated features that form context-dependent configurations [14, 15], viewed as holistic entities [16, 17]. Identifying such configurations helps to understand relationships between organizational characteristics [18], as well as to provide a means of assessing organizational performance. This contrasts with traditional methods of evaluating impacts of organizational models focusing only on individual features of organizations [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this approach, organizations are characterized by interrelated features that form context-dependent configurations [14, 15], viewed as holistic entities [16, 17]. Identifying such configurations helps to understand relationships between organizational characteristics [18], as well as to provide a means of assessing organizational performance. This contrasts with traditional methods of evaluating impacts of organizational models focusing only on individual features of organizations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using configurational approaches have focused on different dimensions or organizational components, such as organizational differentiation, integration and centralization [19], staffing, scope of practice and work environment [20], or processes, structure, environmental factors and strategy [18]. Lamarche et al [14] analyzed primary care medical practices based on four organizational components: 1) the organization’s vision , that includes beliefs, representations, values and goals that allow actors to communicate and assign meaning to their actions, 2) its resources , that relate to the quantity and quality of resources used in carrying out activities, 3) its structure , which includes laws, rules, conventions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-leadership LTCFs with a coefficient value of −0.03 exhibit biased valuation of IPC monetary spending, whereas hybrid-oriented organizations (the coefficient value of 0.14) appear biased in measuring probabilities. The literature notes that cost leaders in hospitals mainly focus on cost control and the efficiency of existing operations [ 46 , 47 ]. Similarly, our findings show that administrators of cost-oriented organizations think about the consequences of COVID-19 risk in a loss-averse way.…”
Section: Discussionmentioning
confidence: 99%
“…Actual measures and actions may depend on different regions and facilities [ 44 ]. In the hospital setting, the extant literature identifies that organizational variables, such as strategy types [ 45 , 46 , 47 ] or business environments and contexts [ 48 , 49 ], affect managerial decisions and performance. Similarly, organizational characteristics and strategy types of LTCFs should be considered in managers’ decision-making, given the complex political, legal, societal, business, and financial environments created by COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One reason could be the mutually reinforcing benefits of a hospital's emphasis on product, services, quality, process innovation, and cost control. Prior research has shown that hospitals can pursue a hybrid strategy successfully with potentially better financial outcomes than those pursuing a pure generic strategy (31,44,49). Thus, we propose that:…”
Section: Original Articlementioning
confidence: 99%